Pengembangan Pendidikan Karakter di TPA (Taman Pendidikan Al-Qur’an) Ittihadil Ummah Karang Anyar Kota Mataram - Muhammad Fahrurrozi (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2020)
In achieving the goals of national education, strengthening character education is a very important an effort to do. Character education must be instilled in humans so that it can become the main foundation for shaping the character of the nation. Given the importance of character education, teachers must work hard in introducing and developing character education for students. One form an effort to improve the character of students in schools is through the habituation of noble moral habits. The purpose of this study was to determine the development of character education in the plan to strengthen character education at TPA Ittihadil Ummah Kr Anyar through habituation of noble moral habits. The method in this research using descriptive qualitative and data collection through the stages of observation, interviews, library research. Data analysis was carried out by data analysis and concluding. The result of this studi indicate that: The character education improvement program at TPA Ittihadil Ummah Kr Anyar is carried out by combining the learning process with the habits of high moral values in everyday life. The result of this studi indicate tha the noble moral habits practiced in the school environment are an effective model for enhancing the character of students